Achieving strategic fit in onion seed supply chain. Issue 2 (14th November 2016) - Timsina, Krishna P.; Bastakoti, Ram C.; Shivakoti, Ganesh P.
Abstract : Purpose: The analysis focuses on the perspective of overall strategic fit in the supply chain of onion seed in Nepal. The purpose of this paper is to analyze current status of onion seed sector in Nepal from the perspective of selected functional strategies that fit in supply chain, and also identifies how various actors involved coordinate among each other. Design/methodology/approach: The integrated approach has been used. It is an actor-oriented approach used to trace product flows. Supply chains generally include several actors for the onion seeds supply chain in Nepal, all those actors may or may not be applicable. However, initial approach would be to first look for these actors then subsequently identify existing supply and its actors. Some traditional methods of product and market analysis isolate operational costs along various stages of production. But, this paper used more comprehensive methodology that has taken into account an entire spectrum of associated activities and inputs. Findings: Result revealed that the market actors of supply chain are taking significant benefit of value addition due to more investment in value creation. Vertical coordination is completely absent and the existence of horizontal coordination is in fragile form. The functional strategies in the upstream as well as the market side are not properly matching with the preference of the downstream actors of supply chain. It is suggested that the supply chain activities should work with different functional strategies such as proper drying and storage of seed and production of preferred varieties to satisfy the need of end consumers. Research limitations/implications: It covers a single crop. Originality/value: The findings and methodological discussions aim at providing practical guidance for supply chain researchers on how to analyze the strategic fit in supply chain.